EDUCATION OF PHYSICAL QUALITIES OF SCHOOLCHILDREN (Educator Insights: Journal of Teaching Theory and Practice, 2025)
The article discusses the relationship between the structural foundations of the development of physical qualities and progressive morphological and biochemical changes in the musculoskeletal system, central and peripheral nervous systems, and internal organs, as well as the methodology for educating the physical qualities of senior schoolchildren.